Potential Inversion Problems for Coupled System of Downgoing and Upcoming One-Way Wave Equations (Journal of Computational Mathematics, 2021)
By using wave splitting method the formulation of the two-dimensional potential inversion problem is set up in terms of the coupled system for downgoing and upcoming wavefields. The boundary conditions on the characteristic surface needed for solving the problem are derived by singularity analysis. Two stability theorems are given for the direct problems of the system treated as Cauchy problems in the direction of depth.
Keywords: 2-D potential inversion; Wave splitting; Singularity analysis.